Potential of AM fungi (Glomus mosseae and Acaulospora laevis) and Trichoderma viride in enhancing growth and development of Eclipta alba (L.) Hassk - and ASHOK AGGARWAL*, CHHAVI MANGLA, ADITYA KUMAR (Indian Phytopathology, 2010)
An attempt was made to study the effect of selected arbuscular mycorrhizal (AM) fungal species (Glomus mosseae & Acaulospora laevis) in different combinations with Trichoderma viride on growth and biomass of Eclipta alba in green house conditions. The study revealed improved growth of all the seedlings inoculated with AM fungi. A prominent improvement in growth parameters was observed after 60 and 90 days. A. laevis alone showed best increment in leaf area while its combination with T. viride was found to be most effective in enhancement of shoot and root length. Chlorophyll content increased significantly in seedlings treated with dual combination of G. mosseae and T. viride. The total shoot and root (fresh and dry) weight and AM association (% root colonization and spore number) also increased in all the inoculated seedlings after 60 and 90 days.